Role of brassinosteroid signaling in modulating Tobacco mosaic virus resistance in Nicotiana benthamiana - Deng, Xing-Guang; Zhu, Tong; Peng, Xing-Ji; Xi, De-Hui; Guo, Hongqing; Yin, Yanhai; Zhang, Da-Wei; Lin, Hong-Hui (Scientific reports, 2016)
Plant steroid hormones, brassinosteroids (BRs), play essential roles in plant growth, development and stress responses. However, mechanisms by which BRs interfere with plant resistance to virus remain largely unclear. In this study, we used pharmacological and genetic approaches in combination with infection experiments to investigate the role of BRs in plant defense against Tobacco Mosaic Virus (TMV) in Nicotiana benthamiana . Exogenous applied BRs enhanced plant resistance to virus infection, while application of Bikinin (inhibitor of glycogen synthase kinase-3), which activated BR signaling, increased virus susceptibility. Silencing of NbBRI1 and NbBSK1 blocked BR-induced TMV resistance and silencing of NbBES1/BZR1 blocked Bikinin-reduced TMV resistance. Silencing of NbMEK2, NbSIPK and NbRBOHB all compromised BR-induced virus resistance and defense-associated genes expression. Furthermore, we found MEK2-SIPK cascade activated while BES1/BZR1 inhibited RBOHB-dependent ROS production, defense gene expression and virus resistance induced by BRs. Thus, our results revealed BR signaling had two opposite effects on viral defense response. On the one hand, BRs enhanced virus resistance through MEK2-SIPK cascade and RBOHB-dependent ROS burst. On the other hand, BES1/BZR1 inhibited RBOHB-dependent ROS production and acted as an important mediator of the trade-off between growth and immunity in BR signaling.